Study on the mechanism of Dexmedetomidine’s effect on postoperative cognitive dysfunction in elderly people - Cai, Yuanbin; Yu, Fan; Wu, Wei; Chen, Wurong (Frontiers in Physiology, 2025)
Postoperative cognitive dysfunction (POCD) is a common complication among elderly patients following surgical procedures, significantly impairing postoperative recovery and quality of life. The selection and dosage of intraoperative anaesthetic drugs are frequently implicated as contributing factors in the development of POCD. In recent years, dexmedetomidine (DEX), a novel α2-adrenoceptor agonist, has been increasingly utilized in surgical anaesthesia for elderly patients, showing potential as both a preventive and therapeutic agent for POCD. This paper provides a comprehensive review of current research on the mechanisms by which DEX affects POCD in the elderly. Additionally, it explores DEX’s mechanisms of action in the context of neuroprotection, anti-inflammation, antioxidative stress, and the regulation of apoptosis, autophagy, and analgesia. The objective is to provide reliable theoretical support and a reference point for the clinical application of DEX in POCD among the elderly, thereby promoting its broader use in clinical practice to improve outcomes and enhance quality of life.